To quit or not: Vulnerability of women to smoking tobacco. (2nd January 2016) - Park, Se-Jung; Yi, Bitna; Lee, Ho-Sun; Oh, Woo-Yeon; Na, Hyun-Kyung; Lee, Minjeong; Yang, Mihi
ABSTRACT: Tobacco smoking is currently on the rise among women, and can pose a greater health risk. In order to understand the nature of the increase in smoking prevalence among women, we focused on the vulnerability of women to smoking behaviors—smoking cessation or tobacco addiction—and performed a systematic review of the socioeconomic and intrinsic factors as well as tobacco ingredients that affect women's susceptibility to smoking tobacco. We observed that nicotine and other tobacco components including cocoa-relatives, licorice products, and menthol aggravate tobacco addiction in women rather than in men. Various genetic and epigenetic alterations in dopamine pathway and the pharmaco-kinetics and -dynamic factors of nicotine also showed potential evidences for high susceptibility to tobacco addiction in women. Therefore, we suggest systemic approaches to prevent tobacco smoking–related health risks, considering gene–environment–gender interaction.